2001
DOI: 10.1021/bi010940b
|View full text |Cite
|
Sign up to set email alerts
|

A Kinetic Analysis of the Catalase Activity of Myeloperoxidase

Abstract: The predominant physiological activity of myeloperoxidase is to convert hydrogen peroxide and chloride to hypochlorous acid. However, this neutrophil enzyme also degrades hydrogen peroxide to oxygen and water. We have undertaken a kinetic analysis of this reaction to clarify its mechanism. When myeloperoxidase was added to hydrogen peroxide in the absence of reducing substrates, there was an initial burst phase of hydrogen peroxide consumption followed by a slow steady state loss. The kinetics of hydrogen pero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 42 publications
1
67
0
2
Order By: Relevance
“…In the absence of other available substrates, heme peroxidases can exhibit a pseudo-catalase activity, where H 2 O 2 is converted into O 2 (54,55). Using an O 2 -electrode, we found that in contrast to catalase, addition of H 2 O 2 to rIDO did not result in a net increase in O 2 levels (Fig.…”
Section: Resultsmentioning
confidence: 81%
“…In the absence of other available substrates, heme peroxidases can exhibit a pseudo-catalase activity, where H 2 O 2 is converted into O 2 (54,55). Using an O 2 -electrode, we found that in contrast to catalase, addition of H 2 O 2 to rIDO did not result in a net increase in O 2 levels (Fig.…”
Section: Resultsmentioning
confidence: 81%
“…Catalase activity of the five Aspergillus strains was determined using Aspergillus niger catalase (Sigma Aldrich) as a standard, the difference in absorbance ( A 240 ) per unit time being a measure of the catalase activity [21]. Elastase activity was quantified using the elastase-specific substrate N-succinylalanyl-alany-prolyl-leucine p-nitroanilide (Sigma Aldrich) [22].…”
Section: Characterisation Of Aspergillus Strainsmentioning
confidence: 99%
“…This reaction prevents accumulation of compound II and the associated inhibition of hypochlorous acid production (18,19). Similarly, reduction of compound II by superoxide boosts the catalytic activity of myeloperoxidase (20). …”
mentioning
confidence: 99%